AN ANALYSIS OF CHARACTERIZATION AND LIBERAL FEMINISM VALUES OF THE MAIN CHARACTER “BELLE” IN THE BEAUTY AND THE BEAST 2017 MOVIE - Kesuma, Dewi; Susilowati, Endang (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2023)
This study analyzes the characterization and liberal feminism values of the main character in the 2017 film Beauty and The Beast by Bill Condon. Liberal Feminism is a goal that places a role in which women can enjoy total freedom and individual freedom. The primary source of this study is taken from movie and screenplay and subtitled. The secondary source of this study is taken from relevant books and the internet. The researcher uses feminist analysis, this analysis can be used to examine the type of film title "Beauty and The Beast 2017 film" which answers various evidence of a woman's struggle against her rights. The researcher selects research methods in Beauty and The Beast 2017 movie through qualitative methods: observation, document study, collection, identifying, and analyzing method used in this study is document study. The researcher explains how the character and characterization of the main character in the film, namely "Belle" is a representation of a woman who is a feminist. She refuses to be treated specially by a man named Gaston. Belle is able to show that she is a girl who can determine the future of her own love journey without depending on any man even though that man has power. After knowing about the character and characterization from the film, we can know the liberal feminist values occur in the film of Beauty and The Beast 2017. The researcher concludes that the characterization of Belle such as smart and progressive, independent, brave and decisive can determine the liberal feminist values contained in the 2017 film Beauty and The Beast.